Coating of AFM probes with aquatic humic and non-humic NOM to study their adhesion properties - Aubry, C.; Gutierrez, L.; Croue, Jean-Philippe (2013)
Atomic force microscopy (AFM) was used to study interaction forces between four Natural Organic Matter (NOM) samples of different physicochemical characteristics and origins and mica surface at a wide range of ionic strength. All NOM samples were strongly adsorbed on positively charged iron oxide-coated silica colloidal probe. Cross-sectioning by focused ion beam milling technique and elemental mapping by energy-filtered transmission electron microscopy indicated coating completeness of the NOM-coated colloidal probes. AFM-generated force-distance curves were analyzed to elucidate the nature and mechanisms of these interacting forces. Electrostatics and steric interactions were important contributors to repulsive forces during approach, although the latter became more influential with increasing ionic strength. Retracting force profiles showed a NOM adhesion behavior on mica consistent with its physicochemical characteristics. Humic-like substances, referred as the least hydrophilic NOM fraction, i.e., so called hydrophobic NOM, poorly adsorbed on hydrophilic mica due to their high content of ionized carboxyl groups and aromatic/hydrophobic character. However, adhesion force increased with increasing ionic strength, suggesting double layer compression. Conversely, polysaccharide-like substances showed high adhesion to mica. Hydrogen-bonding between hydroxyl groups on polysaccharide-like substances and highly electronegative elements on mica was suggested as the main adsorption mechanism, where the adhesion force decreased with increasing ionic strength. Results from this investigation indicated that all NOM samples retained their characteristics after the coating procedure. The experimental approach followed in this study can potentially be extended to investigate interactions between NOM and clean or fouled membranes as a function of NOM physicochemical characteristics and solution chemistry.